2022
DOI: 10.1111/bre.12666
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and geological controls of the seabed fluid flow system, the central‐western Bohai Sea: A general overview

Abstract: Thorough understanding of seabed fluid flow system is of great significance to geohazard identification and hydrocarbon exploration as it can reshape the seabed and act as an indicator of subsurface hydrocarbon resources. For the first time, an integrated study of side‐scan sonar, single‐ and multi‐channel seismic data and magnetic data reveals a complex fluid flow system composed of various seafloor expressions (i.e. pockmarks and mounds) and shallow fluid migration pathways in the central‐west Bohai Sea off … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 145 publications
0
4
0
Order By: Relevance
“…The data in the study area are two-dimensional single-channel seismic data, lacking the constraints of other data types, and the plane distribution characteristics of the depressions on profiles are unclear, which will be uniformly interpreted as pockmarks. Duan et al (2022) confirmed that there are indeed pockmarks caused by fluid escape in the Bohai Sea. The pockmarks identified in the study area are divided into U-shaped pockmarks, Vshaped pockmarks and asymmetric pockmarks according to the morphology of the seismic profile (Figure 2).…”
Section: Pockmarksmentioning
confidence: 58%
See 2 more Smart Citations
“…The data in the study area are two-dimensional single-channel seismic data, lacking the constraints of other data types, and the plane distribution characteristics of the depressions on profiles are unclear, which will be uniformly interpreted as pockmarks. Duan et al (2022) confirmed that there are indeed pockmarks caused by fluid escape in the Bohai Sea. The pockmarks identified in the study area are divided into U-shaped pockmarks, Vshaped pockmarks and asymmetric pockmarks according to the morphology of the seismic profile (Figure 2).…”
Section: Pockmarksmentioning
confidence: 58%
“…Duan et al. (2022) confirmed that there are indeed pockmarks caused by fluid escape in the Bohai Sea. The pockmarks identified in the study area are divided into U‐shaped pockmarks, V‐shaped pockmarks and asymmetric pockmarks according to the morphology of the seismic profile (Figure 2).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Recently, we reveal a complex seabed fluid flow system composed of various seafloor expressions (i.e. mounds and pockmarks) and shallow fluid migration pathways in the central-west Bohai Sea based on an integrated study of side-scan sonar, single-and multi-channel seismic data and magnetic data (Duan et al, 2022).…”
Section: Seabed Fluid Flow In the Bohai Seamentioning
confidence: 99%